ANALISIS PENGARUH KONDISI OPERASI LEAN TEG TERHADAP KINERJA DEHIDRASI GAS PRODUKSI UNTUK PENCEGAHAN PEMBENTUKAN HIDRAT MENGGUNAKAN TRIETHYLENE GLYCOL (TEG) - ihzaganda, caesar; Triono, Agus (Universitas Jember, 2026)
Gas production generally contains water vapor that can cause operational problems such as corrosion, reduced gas quality, and hydrate formation. Therefore, a dehydration process is required to reduce water content and meet sales gas specifications. This study aims to analyze the effect of operating conditions on gas dehydration performance using Triethylene Glycol (TEG) and to determine the most suitable property package in Aspen HYSYS simulation. The methodology includes literature study, field data collection, process modeling, and simulation analysis using Peng-Robinson and Glycol Package. The parameters analyzed are pressure, temperature, and TEG circulation rate. The results show that the Peng-Robinson property package provides simulation results closer to actual field conditions with outlet water content of 0.96 kg/h compared to 0.9 kg/h in actual data. Increasing pressure tends to increase water content in gas, while optimal temperature and TEG circulation improve dehydration efficiency. It can be concluded that proper selection of thermodynamic models and operating parameters significantly affects dehydration performance and hydrate prevention.